Between Competitiveness and Sustainability? Achievements and Dilemmas of Regional Policy in the Context of Economic Development of Rural Regions: the Case of Poland - Dudek, Michał; Wrzochalska, Agnieszka (European Journal of Sustainable Development, 2019)
A clear long-term economic trend is the concentration of capital and settlement. These processes increasingly include development centres located in cities and their functional areas. In turn, many peripheral areas, including rural areas, are subject to socio-economic marginalization. As a result, the inter-regional and intra-regional disparities in wealth and quality of life become more visible and deepen. Increasing spatial differences are confront with numerous scientific explanations and remedies, which usually are translated into different strategies and practices of regional policy. Regional policy actions assume a different scope, objectives, instruments of intervention and could be categorized as a policy based on the paradigm of competitiveness (polarisation) or sustainability. The aim of the paper was to determine the level of economic disparities between urban and rural regions in Poland in the context of assessment of implemented regional policy. In the paper selected approaches to supporting rural development in regional policy, namely the perspectives based on the paradigm of competitiveness and sustainability were characterised. The analyses carried out documented the differences in the intensity of support of EU Cohesion Policy tools per capita in favour of urban regions. Even though the value of financial support from EU funds was positively correlated with the level of regional development, there was no statistically significant impact of this intervention on the processes of economic convergence and divergence. The conclusions presented in the study were based on the analysis of the Eurostat data gathered for 72 Polish sub-regions in 2007-2015. For the purpose of the study the statistical methods (i.e. descriptive statistics, measures of economic convergence), as well as the content analysis of strategic documents were used. Key words: rural regions, competitiveness, sustainability, economic development, regional policy